Gravebooks - White, J. A. (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2022)
"Alex again has to write stories to survive, this time learning to finish discarded ideas and overcome writer's block, after he's held hostage in his dreams by fear vampire Simeon, working alongside evil witch Natacha in a story graveyard"--Provided by publisher.
Sequel to: Nightbooks.
5-8.
English.
Keywords: Authorship -- Juvenile fiction; Creative ability -- Juvenile fiction; Fear -- Juvenile fiction; Magic -- Juvenile fiction; Vampires -- Juvenile fiction; Authorship -- Fiction; Creative ability -- Fiction; Fantasy; Fear -- Fiction; Magic -- Fiction; Vampires -- Fiction; Authorship -- Fiction; Creative ability -- Fiction; Fear -- Fiction; Magic -- Fiction; Vampires -- Fiction; Fantasy fiction